The Effect of Mudharabah Financing and Musyarakah Financing on Profitability Ratios at PT. Bank BRI Syariah TBK Period 2012-2018 - norma sari; budi gautama; damri batubara; nando pahrizal (Journal Of Sharia Banking, 2020)
The background problem in this research is mudharabah financing and musyarakah financing experiencing fluctuations that are not followed by Return On Assets (ROA), which in accordance with the theory of increased financing, the Return On Assets (ROA) vice versa. The formula in this research is whether there is an influence of mudharabah financing and musyarakah financing on Return On Assets (ROA) at PT. Bank BRI Syariah TBK partially or simultaneously. This research is a quantitative descriptive study, the sample used as many as 36 samples with a purposive sampling design, data obtained through the website www.OJK.go.id testing in this study is to use the SPSS computer program Version 23. The results showed that partially there was the influence of mudharabah financing on Return On Assets (ROA) at PT. Bank BRI Syariah Tbk, and Musharaka financing shows that musyarakah financing partially influences Return On Assets (ROA) at PT. Bank BRI Syariah Tbk. With the results of the F test influential in the level of sig. So the hypothesis (Ha3) is accepted. So it can be concluded that simultaneously there is an influence between mudharabah financing and musyarakah financing on Return On Assets (ROA). While the R2square determination test is 33 percent while the remaining 67 percent is influenced by other factors not included in this study.